Development of parenting self-efficacy in mothers of high-risk infants. (February 2020) - Vance, Ashlee J.; Pan, Wei; Malcolm, William H.; Brandon, Debra H.
Abstract: Purpose: The aim of this prospective, longitudinal study was to (1) examine the development of parenting self-efficacy (PSE), (2) explore the influence of contextual factors (e.g., family functioning, family centered care, and infant medical caregiving complexity) on PSE development, and (3) whether PSE and contextual factors predict parent and infant health outcomes in a high-risk infant population. Method: Mothers ( n  = 67) of infants diagnosed with a complex medical condition following birth were enrolled within 3 weeks of their infant's diagnosis and admission to intensive care. Participants completed an online study survey at study enrollment (T1), infant discharge (T2), and 3 months after discharge (T3). Change in PSE was examined using mixed modeling and predictors of parent and infant health outcomes were explored using multiple regression. Results: PSE significantly increased over time (b = 2.08, p  < .0001). Family functioning was the only significant contextual factor, where worse family functioning at enrollment was associated with lower confidence over time. Mothers who were older and had more than one child were significant predicators of higher PSE. Interestingly, being married, compared to being single, was associated with decreased PSE. Higher PSE was also predictive of positive maternal psychological wellbeing at 3 months after discharge and a decrease in infant's medical complexity was associated with higher maternal psychological well-being. Conclusion: These are important findings given that PSE is known to contribute to infant development and health status. Highlights: Parenting self-efficacy (PSE) increased over time among mothers of infants with medical complexity. Family functioning, age, and having children predicted higher PSE, while marital status was associated with lower PSE. Further research is needed to explore common patterns in PSE development.